Review of Wolf Schmid, Figurally Colored Narration. Case Studies from English, German, and Russian Literature (De Gruyter, 2022) (ENTHYMEMA, 2023)
Review of Wolf Schmid, Figurally Colored Narration. Case Studies from English, German, and Russian Literature (De Gruyter, 2022).